(untitled) (Communications in Mathematical Research, 2021)
In this paper, we establish a fixed point theorem for set-valued mapping on a topological vector space without "local convexity". And we also establish some generalized Ky Fan's minimax inequalities for set-value vector mappings, which are the generalization of some previous results.